Research on Hydraulic System Optimization of Loader Based on GA-BP - Hua, Zhang; Lei, Zhao; Hua, Chen (Manufacturing Technology Journal, 2019)
Aiming to study the working efficiency and stability of the loader, the hydraulic system of the loader is studied. Taking the ZL50 loader as the research carrier, the working conditions of the loader and the working principle of the hydraulic system are analysed at first. AEMSim software is used to simulate and analyse the hy-draulic system, and the necessity of using the algorithm to optimize the hydraulic system is put forward. Secondly, the mathematical model of key hydraulic system optimization is deduced, and genetic algorithm and neural net-work algorithm are used to optimize the analysis of the objective function, and the simulation results are compared and analysed again. The results show that the parameters optimized by GA and BP algorithm are better than the original parameters. Further analysis shows that the parameters optimized by GA algorithm are better than BP algorithm in smoothness.
Keywords: Loader; Hydraulic system; Simulation; Genetic Algorithm; Optimization analysis